Evaluation of demands and needs for dental care in a sample of the Turkish population - (:unkn) unknown (My University, 2010)
OBJECTIVES: To evaluate the demands and needs for dental care and to identify the level of dental and periodontal status in patients of different age groups visiting the Faculty of Dentistry, Marmara University, Istanbul, Turkey. METHODS: A total of 1000 first-visit patients (517 female and 483 male) were examined and questioned. The main complaint of each patient was recorded and considered to be a measure of demand for dental care. The World Health Organization's (WHO) basic methods were used to determine the tooth-based and orthodontic normative treatment needs. Periodontal status was determined by using the Community Periodontal Index of Treatment Needs (CPITN). In addition, prosthetic normative needs were assessed. RESULTS: This study showed that patients in different age groups required different treatments and had different main complaints. In total, 89.3, 74.1 and 57.7% of the patients named periodontal, restorative and prosthetic care as their main complaint, respectively. Approximately 21% of the total did not need restorations and extractions, and only 12% of the sample did not have a normative periodontal treatment need. About half of subjects needed fixed partial dentures. CONCLUSIONS: Normative treatment needs of patients were very high. Therefore, a new national strategy for oral health must be devised for Turkey. This study can assist in setting the baseline for that strategy.
Keywords: Dental treatment demands; Oral hygiene; Periodontal status; Treatment needs